Mycobacterium tuberculosis modulates NUDT21-mediated alternative polyadenylation to enhance FTH1 expression in macrophages and promotes intracellular growth - Liu, Xiaoqian; Cai, Ningjian; Dai, Youchao; Chen, Xinchun; Zeng, Xiaobin (Frontiers in Cellular and Infection Microbiology, 2025)
Ferritin heavy chain 1 (FTH1) is a key iron-storage protein that regulates iron availability, supports immune defense, and prevents iron-induced toxicity. During Mycobacterium tuberculosis (Mtb) infection, macrophages enhance FTH1 expression to sequestrate iron and limit Mtb growth. However, Mtb can exploit the host ferritinophagy pathway to degrade FTH1 and release iron, thereby promoting its survival. Although FTH1 plays an essential role in host–pathogen interaction during Mtb infection, its regulation remains unclear. Previous studies suggest that post-transcriptional mechanism, particularly alternative polyadenylation (APA), are critical in immune responses. We propose that APA, which determines the length of a transcript’s 3′UTR, may regulate FTH1 expression during Mtb infection. Our study demonstrates that Mtb induces APA of FTH1 in macrophages, favoring the production of longer isoforms that enhance protein synthesis. Mechanistically, Mtb disrupts the interaction between NUDT21 and CPSF6, impairing NUDT21’s ability to bind UGUA motifs in the FTH1 3′UTR, a key step in polyadenylation site selection. Silencing NUDT21 reduces macrophage bactericidal activity against Mtb, highlighting its role in immune defense. These findings reveal a novel Mtb-driven mechanism that enhances FTH1 expression via the NUDT21-mediated APA pathway in macrophages, suggesting that Mtb manipulates this process to promote its survival. This study provides new insights into tuberculosis pathogenesis and points to potential avenues for therapeutic exploration.